P125 Balance impairment and clinical associations in individuals with COPD: a systematic review with meta-analysis. (December 2018) - Loughran, KJ; Atkinson, G; Beauchamp, MK; Dixon, J; Martin, D; Rahim, S; Harrison, SL
Abstract : Introduction: People with Chronic Obstructive Pulmonary Disease (COPD) are four times more likely to fall than healthy peers, leading to increased morbidity, mortality and healthcare costs. Balance impairment in COPD has been linked to falls but the degree of balance dysfunction and mechanisms underlying such impairment in COPD are unknown. We conducted a systematic review to establish 1. the extent to which balance is impaired in COPD compared to healthy controls and 2. to determine the clinical factors that may contribute to balance impairment in COPD. Methods: We undertook a search of five electronic databases, of studies comparing individuals with COPD and healthy controls that measured static or dynamic balance. Meta-analysis was possible on three clinical balance measures which were assessed in five or more studies. A meta-regression using difference in% predicted FEV 1 as an indicator of disease severity was conducted. Finally, we performed a meta-analysis on correlation data of balance impairment and reduced quadriceps strength; the only associated factor assessed in five studies. A narrative summary was conducted when meta-analysis was not possible. Results: 3904 records were identified after de-duplication. 75 full texts were screened, with 23 studies included in the quantitative synthesis. People with COPD performed worse than healthy controls on Timed Up and Go (p≤0.005, 95% CI 0.964 to 2.257 s), Single Leg Stance (p=0.001, 95% CI −2.983 to −0.775 s) and Berg Balance Scale (p≤0.005, 95% CI −2.238 to −1.021), with large effect sizes (standardised difference in means=1.746, 1.879 and 1.630 respectively). There was no effect of disease severity. There was a weak to moderate association between clinical balance outcomes and reduced quadriceps strength (r=0.370, p≤0.005). Individual study results suggest balance impairment is associated with reduced physical activity and exercise capacity. Conclusions: People with COPD have large deficits in their balance compared to healthy controls and this appears related to reduced quadriceps strength, physical activity and exercise capacity. These factors are modifiable with exercise interventions and the findings of this review can be used to inform tailored interventions for balance impairment and supports that assessment and management of balance should be part of COPD care guidelines.